The studies on the rate of sedimentation at Bekok Dam using hydrographic technique - Mahmud, Mohd. Razali; Othman, Rusli; Din, Usmuni; Mardi, Ahmad ShahIan (1995)
A derailed investigation is carried out into the method of hydrograph" surveying to determine the rate of sedimentation on the riverbed. For this purpose, Bekok Dam is chosen as a suitable site for the research mainly due to the fact that the dam is suspected facing serious sedimentation problems from one of its tributaries. Three epochs observations were taken over a period of one year. The technique involves using conventional positioning and sounding system. Furthermore, the lead line technique of determining depth is also used mainly as a check on the depth nh1ained using normal echo sounder. The data set comprises of hydrographic surveys which were obtained by running the survey boat on a 5 metres sounding lines. Three separate hydrographic plans which were produced haved on the three epoch of observations were plotted on a scale of 1:2000 It wm found (hal the technique of hydrographic surveying could be used to compute the rate of sedimentation on the riverbed at an accuracy as required.